Tomography For Electrical Impedance: An Alternative Method For Monitoring Joint Injuries - Muñoz Sánchez , Juan David; Mosquera Leyton, Víctor Hugo (Ingeniería Solidaria, 2020)
Introduction:This review article shows the state of the art of different techniques for monitoring joint injuries. This work is the product of the research project "Viability of electrical impedance tomography for the monitoring of joint injuries", which took place at the University of Cauca during the period 2018-2019. Aim:Identify non-invasive bio-image methods that are used in the evaluation of joint diseases. Methodology: Selection and review of papers related to the evaluation of joint injuries using non-invasive bio-image technologies using systematic mapping. Results: Magnetic resonance and computed tomography systems make up the non-invasive methods of greater reliability and application in the evaluation of joint injuries. Similarly, some studies show good results from other methods such as systems based on bio-impedance when monitoring the deterioration of joint cartilage. However, electrical impedance tomography (EIT) devices have not yet been widely studied in the joint injuries evaluation. Conclusion: Electronic prototypes of low-cost electrical impedance tomography have been developed that have allowed for the detection and recognition of gestures made by hand from the analysis of the distribution of conductivity in the wrist joint, which allows us to infer that EIT could be a good alternative for the monitoring of joint injuries. Originality: The literature does not show studies focused on the development and implementation of EIT systems in medical applications related to joint injuries. Limitations: This review paper only mentions those studies that describe the non-invasive bio-image methods used to evaluate joint diseases, including the medical applications of EIT systems.